Human-Oriented Leadership and Organizational Commitment in US Subsidiary Company Based in Sarawak - Azman Ismail; Yusniati Ishak; Munirah Hanim Yusuf (Binus Business Review, 2016)
This article was conducted to examine the relationship between human-oriented leadership (HOL) and organizational commitment. A survey method was employed to obtain data from the employees of one US subsidiary companybased in Sarawak. Results of the Partial Least Squares (SmartPLS) model analysis confirmed that participative leadership, supportive leadership, and empowerment act as important antecedents of organizational commitment.These findings reveal that the capability of managers practicing HOL styles (supportive, participative, and empowerment) has enhanced employees’ commitment to the organization.